? asked in Science & MathematicsMathematics · 7 years ago

limit of x as it approaches infinity (x^2+sinx)/(x^2+1)?

HELP please provide a clear and detailed explanation

5 Answers

Relevance
  • 7 years ago
    Favorite Answer

    Look at the numerator. It fluctuates between x^2 - 1 and x^2 + 1 because sinx oscillates between -1 and +1.

    Observe that the limit of (x^2 + 1) / (x^2 + 1) = 1 for all values of x.

    Now look at (x^2 - 1) / (x^2 + 1) = (x^2 + 1 - 2) / (x^2 + 1) because x^2 - 1 = x^2 + 1 - 2.

    (x^2 + 1 - 2) / (x^2 + 1) = (x^2 + 1) / (x^2 + 1) - 2/(x^2 + 1) = 1 - (2/(x^2 + 1))

    As x approaches infinity, 1 - (2/(x^2 + 1) = 1 - 0 = 1.

    So, we now have:

    f(x) = (x^2 - 1) / (x^2 + 1)

    g(x) = (x^2 + 1) / (x^2 + 1)

    h(x) = (x^2 + sin x) / (x^2 + 1)

    Observe that f(x) < h(x) < g(x)

    Observe that lim f(x) = 1 = lim g(x) as x approaches infinity.

    Therefore, the lim h(x) = 1 as x approaches infinity by the Squeeze Theorem

  • Anonymous
    7 years ago

    1

  • 7 years ago

    Lim x->~ (x^2+sinx)/(x^2+1) (devide all by x^2)

    Lim x->~ 1+(sinx/x^2)/(1+1/x^2) = 1+0/1+0 = 1

    remeber if sinx/x^2 will become 1/x

    as sina/a = a/a = 1

    so sinx/x^2 = x/x * 1/x =1/x which value of 1/x is 0

  • 5 years ago

    Apply L Hospital rule and get limit x tends to infinity (2x + cos x)/2x. Split the limit to get limit x tends to infinity 1 which is 1, plus limit x tends to infinity cos x/x which is equal to product of 0 and a finite number between -1 and 1, that is 0. Hence answer is 1

  • How do you think about the answers? You can sign in to vote the answer.
  • 4 years ago

    To sum all of it up basically because of fact ? is to the means of 0,?^0, we can not say that the lim as x has a tendency to ? is a million for x^(a million/x) because of fact we don't understand that's extra effective, the 0 or the ?. hence we ought to remedy it utilising L'Hospitols (L'H) rule. lim x^(a million/x) = ?^0 x->? enable y= lim x^(a million/x) x->? lny = lim ln(x^(a million/x) x->? utilising ln regulations we pull out the a million/x lny = lim (ln(x))/x = ?/? x->? Now we are able to L'H L'H lny = lim (a million/x)/a million = 0 x->? lny = 0 e^lny = y = e^0 = a million hence we are able to now genuine say that the lim x^(a million/x) = a million x->?

Still have questions? Get your answers by asking now.